Nouvelles Du Monde (Fiep Bulletin - online, 2015)
Le departement de l’éducation, des Arts et la Science, à Pretoria; Private Bag 122 a édite les Manuel Suivants: Gymnastics for senior boys. Boxing, wresthing, athletics. Aparatus Gymnastics. Physical Education for Girls. Physical Education for boys.